OPTIMALISASI LOKASI PENANAMAN RUMPUT LAUT KAPPAPHYCUS ALVAREZII UNTUK MENINGKATKAN KELANGSUNGAN HIDUP, PETUMBUHAN MUTLAK DAN KANDUNGAN KARAGENAN - Graselia Fallo; Ade Yulita H. Lukas; Welem Linggi Turupadang (Nusa Cendana University, 2026)
Kappaphycus alvarezii is a high-value seaweed commodity widely cultivated as a primary source of carrageenan. The success of its cultivation is strongly influenced by environmental conditions, including the planting distance from the shoreline, which may affect water quality and growth performance. This study aimed to assess the effect of different planting distances on growth, survival rate, and carrageenan content of K. alvarezii. The experiment was conducted for 45 days in Oenaek waters using a Completely Randomized Design (CRD) with three treatments and three replicates, namely planting distances of 100 m (A), 300 m (B), and 500 m (C) from the shoreline. Data were analyzed using ANOVA, followed by post-hoc tests at a 95% confidence level when significant differences were observed. Results revealed that planting distance significantly affected absolute growth (p<0.05), with the highest value recorded in treatment C (500 m) at 163.11 ± 0.31 g. The highest carrageenan content was obtained in treatment B (300 m) at 18.226%, while survival rate reached 100% across all treatments. These findings highlight that planting distance influences both growth and carrageenan yield, suggesting that site selection should be aligned with production objectives, whether to maximize biomass or optimize carrageenan content. Keywords: Kappaphycus alvarezii, survival, absolute growth, carrageenan, water quality